Mapping the Relationship between Ownership Structure and Firm Performance: A bibliometric analysis of Web of Science and Scopus databases (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Mapping the Relationship between Ownership Structure and Firm Performance: A bibliometric analysis of Web of Science and Scopus databasesSanjanaDr. Priti SharmaDr. Sanjiv KumarDr. Karambir GuliaThe purpose of the current investigation is to comprehend the topic's history and trend using the technique of bibliometric analysis, delivering crucial background information on the association of ownership structure and company performance. Two renowned and credible databases, Scopus and Web of Science, were employed for this intent so as give readers an enhanced understanding of the topic's fundamental elements. The researcher explored the ways in which the subject's present field has broadened and evolved throughout the period of 1993 to 2022. In accordance to the data, the journal "Corporate Ownership and Control" has the most published papers in this subject area, while "Journal of Corporate Finance" has received the maximum number of citations. “Yoshikawa" was found as the topmost contributing author in the present field of study. The most popular keywords came out to be "agency cost," "ownership structure," "firm performance," and so on. The findings of the present paper can be beneficial for scholars, academicians, policy makers in determining the current trends in the field of governance.